Adaptasi Guru Dalam Menghadapi Administrasi Kurikulum Merdeka di TK Budi Mulia - Anisa Sriwahyuni; Nur Halimah; Nayra Alika Putri Rahma; Tri Yolandya Br. Ginting; Divla Aulia; Reni Zabilah; Sri Indriani Harianja; Laila Fitriana (Ar-Raihanah: Jurnal Pendidikan Islam Anak Usia Dini, 2026)
This study aims to analyze the adaptation process of teachers in dealing with the administrative requirements of the Merdeka Curriculum at TK Budi Mulia, Jambi City. The study focuses on teachers’ adjustment to changes in learning administration, challenges encountered during curriculum implementation, and forms of school support in assisting teachers with administrative tasks. This research employed a qualitative approach using a case study method. The participants consisted of the principal and teachers directly involved in the implementation of the Merdeka Curriculum. Data were collected through observation, interviews, and documentation. The data were analyzed through data reduction, data presentation, and conclusion drawing. The findings revealed that teachers adapted to administrative changes through self-learning, discussions with colleagues, and guidance from school supervisors. The main challenge faced by teachers was not classroom instruction but the increasing administrative workload, including the preparation of teaching modules, child development assessments, portfolios, and narrative reports. Support from the principal, teamwork, and the use of supplementary learning materials helped teachers manage these administrative demands. Therefore, the successful implementation of the Merdeka Curriculum at TK Budi Mulia is influenced by teachers’ adaptability and support from the school environment